Molecular basis for disassembly of an importin:ribosomal protein complex by the escortin Tsr2 - Sabina Schütz (Nature Portfolio, 2018)
Ribosomal proteins are transported to the nucleus with the help of importins, from which they are released prior to incorporation into the nascent ribosome. Here the authors report the NMR structure of the ribosomal protein eS26 in complex with the escortin Tsr2 and shed light on the mechanism of eS26 release from importin.